Corpo e beleza: uma análise das produções da educação física, em nível de mestrado - Silva, Liege Monique Filgueiras da (2011)
Talking about body and beauty seems fairly familiar to physical education. We understand that the body language in the area provides many meanings over the appearance, beauty and aesthetics, thus requiring the need of criticism and the need to interrogate her to realize how physical education has been re-signified. For this purpose, considering the multiplicity of meanings that surround the body and beauty, we discussed the implications that this brings to the area of Physical Education, analyzing the conception of body and beauty in the studies in this area, at the masters level, from some questions: What conceptions of body and beauty have been discussed in the studies of physical education at the masters level? What is the relationship between the meanings of body and beauty products analyzed and identified in the models of beauty outlined in Physical Education? We understand the importance of this research and its contribution to the epistemological analysis of existing studies. And, mainly because there is a lack of studies that discuss these productions. For construction of this text and for our reflections, we rely on thoughts like David Le Breton, Claude Levi- Strauss, Michel Foucault, Maurice Merleau-Ponty, Ana Marcia Silva, Carmen Smith, Isabel Mendes, Karenin Porpino Nobrega and flounder. The present study is characterized as a qualitative research, and content analysis proposed by Laurence Bardin (1977) for data processing. The corpus was composed of eight essays in the area of Physical Education, published in the CAPES Theses Database for the period 2004 to 2008, selected from the subject and body beauty. The initial reading allowed us to select meaningful units and guide our discussions on two main themes, which make up the two chapters of the work. In the first chapter, entitled Body, beauty and culture, as evidenced understandings of body, nature and culture that are present in the work is considered. In the second chapter, Standard Body Transformations and beauty, we present the concepts of body and beauty found in the dissertation, focusing on the mutability of representations of the models of beauty in body singularities in the relations of power-knowledge and the importance given the body in society, especially with regard to physical education professionals. We have thus found that, considering the dissertations analyzed, the understanding of body and beauty has been resignified, when dealing with other aesthetic conceptions that consider the uniqueness expressed in the human body and the culture of which the individual belongs